2017
DOI: 10.1155/2017/9783893
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin Treatment Protects against Renal Ischemia-Reperfusion Injury in Rats

Abstract: Renal ischemia-reperfusion (I/R) injury is a common but severe scientific problem. Luteolin has great anti-inflammatory and antioxidant effects. In this study, we studied the effect of luteolin on renal I/R injury in rats. Intragastric administration of luteolin or saline was performed in Sprague-Dawley rats before (40 mg/kg for three days) and after (one day) renal I/R modeling. Kidney and blood samples were harvested to detect the severity of renal injury 24 hours after operation. The results showed that lut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 38 publications
3
39
0
4
Order By: Relevance
“…Recently, it was demonstrated that luteolin effectively suppresses IL-1β, TNF-α, IL-6 and IL-8 secretion from PBMC from healthy donors incubated with LPS [203], confirming reports showing that luteolin reduces IL-6 and TNF-α secretion in LPS-stimulated RAW 264.7 macrophages [190]. Hong et al evaluated the anti-inflammatory effects of luteolin in renal I/R injury in Sprague-Dawley rats and demonstrated that this natural compound attenuated serum and renal TNF-α, IL-1β and IL-6, and the renal HMGB1 and NF-κB expression levels in I/R rats [204]. In addition, luteolin significantly reduced the endoplasmic reticulum stress and renal cell apoptosis caused by renal I/R injury [204].…”
Section: Flavanonessupporting
confidence: 53%
See 1 more Smart Citation
“…Recently, it was demonstrated that luteolin effectively suppresses IL-1β, TNF-α, IL-6 and IL-8 secretion from PBMC from healthy donors incubated with LPS [203], confirming reports showing that luteolin reduces IL-6 and TNF-α secretion in LPS-stimulated RAW 264.7 macrophages [190]. Hong et al evaluated the anti-inflammatory effects of luteolin in renal I/R injury in Sprague-Dawley rats and demonstrated that this natural compound attenuated serum and renal TNF-α, IL-1β and IL-6, and the renal HMGB1 and NF-κB expression levels in I/R rats [204]. In addition, luteolin significantly reduced the endoplasmic reticulum stress and renal cell apoptosis caused by renal I/R injury [204].…”
Section: Flavanonessupporting
confidence: 53%
“…Hong et al evaluated the anti-inflammatory effects of luteolin in renal I/R injury in Sprague-Dawley rats and demonstrated that this natural compound attenuated serum and renal TNF-α, IL-1β and IL-6, and the renal HMGB1 and NF-κB expression levels in I/R rats [204]. In addition, luteolin significantly reduced the endoplasmic reticulum stress and renal cell apoptosis caused by renal I/R injury [204]. Recently, Ding et al demonstrated that luteolin attenuates atherosclerosis in high-fat fed apoE-/-mice by alleviating inflammation through inhibition of signal transducer and STAT3 [205].…”
Section: Flavanonesmentioning
confidence: 99%
“…Reperfüzyon sonucunda dokuda oluşan SOR'lar lipid peroksidasyonuna ve hücre hasarına yol açmaktadır (7). Bu nedenle İ/R hasarının şiddetini azaltmaya yönelik olarak yapılan deneysel çalışmalarda çok sayıda antioksidan ve antiinflammatuar maddenin etkisi araştırılmaktadır (18)(19)(20) (10). Bir başka çalışmada ise nizatidinin MPO-H2O2-Cl-sisteminde üretilen güçlü bir klorlayıcı oksidan olan hipokloröz asiti (HOCl) büyük ölçüde temizlediği ifade edilmektedir (25).…”
Section: Discussionunclassified
“…The grading system was shown as the following scoring: 0 (normal kidney); 1 (0-5% injury, minimal damage); 2 (5-25% injury, mild damage); 3 (25-75% injury, moderate damage); and 4 (75-100% injury, severe damage). 16,17 Immunohistochemistry Immunohistochemical analysis was performed using the Histone Simple Stain Kit (Nichirei, Tokyo, Japan), according to the manufacturer's instructions. Paraffin-embedded sections were deparaffinised with xylene and then rehydrated in a descending series of ethanol washes.…”
Section: Morphologic Analysismentioning
confidence: 99%